2011
DOI: 10.3945/ajcn.110.001867
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cutoffs of percentage body fat for predicting obesity-related cardiovascular disease risk factors in Korean adults

Abstract: Only one-fourth of Korean men had a normal body composition, whereas most of the Korean women had a normal body composition. We conclude that susceptibility to cardiovascular disease and its risk factors is higher in Korean men than in Korean women. The cutoffs are useful for providing adequate guidelines for treating and preventing cardiovascular disease. This was the first study to determine cutoffs of percentage body fat for Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
2
33
0
1
Order By: Relevance
“…The results of the present study clearly indicate that the BF% of Chinese women is, on average, 10% higher than that of Chinese men. This gender variation in BF% is similar to that reported previously for Americans and Koreans . Furthermore, the present data reveal that the BF% of 30–49‐year‐old Chinese women is lower than that of 50–70‐year‐old Chinese women.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study clearly indicate that the BF% of Chinese women is, on average, 10% higher than that of Chinese men. This gender variation in BF% is similar to that reported previously for Americans and Koreans . Furthermore, the present data reveal that the BF% of 30–49‐year‐old Chinese women is lower than that of 50–70‐year‐old Chinese women.…”
Section: Discussionsupporting
confidence: 91%
“…This study was performed to determine the optimal BF percentage cut‐offs to predict an increase in obesity‐related CVD risk factors in Korean adults, based on nationally representative samples with rigorous body composition measurements by DXA. A study of 41 088 Korean adults (18–92 years of age), who underwent routine health check‐ups, claimed that the appropriate BF percentage cut‐off value was 21% for men and 37% for women . However, that study had limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) was defined as fasting blood glucose ≥126 mg/dl or treatment of the disease . Dyslipidaemia was defined as total cholesterol ≥240 mg/dl and/or high‐density lipoprotein (HDL) cholesterol <40 mg/dl and/or triglyceride ≥150 mg/dl or treatment of dyslipidaemia . The CVD risk factors considered for analysis were HTN, DM and dyslipidaemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been infrequently used in research studies because of the high cost and time involved in measurement and the need for highly trained personnel. A recent study 65 used percent body fat as a predictor of obesity-related cardiovascular disease risk factors in Korean adults. Using data from the third National Health and Nutrition Examination Survey, Menke and colleagues 66 reported that waist circumference showed the strongest association with cardiovascular disease risk factors among the five adiposity measurements (BMI, total body fat, percent body fat, skin-fold thickness, waist circumference).…”
Section: Discussionmentioning
confidence: 99%